Rivaroxaban versus standard anticoagulation for symptomatic venous thromboembolism (REMOTEV observational study): Analysis of 6-month outcomes. (1st January 2017) - Gaertner, Sébastien; Cordeanu, Elena-Mihaela; Nouri, Salah; Faller, Alix-Marie; Frantz, Anne-Sophie; Mirea, Corina; Bilbault, Pascal; Ohlmann, Patrick; Le Ray, Isabelle; Stephan, Dominique
Abstract: Background: This study aimed to provide safety and efficacy data of rivaroxaban in routine patient care in a non-selected symptomatic venous thromboembolism (VTE) population. Methods and results: REMOTEV is a prospective, non-interventional study of patients with acute symptomatic VTE, treated with oral rivaroxaban, VKA or parenteral heparin/fondaparinux alone for at least 3 months and who are followed up for 6 months. From Nov. 2013 to July 2015, 499 consecutive patients were retained for baseline analysis and 445 for safety analysis. The mean age was 65.1 years, 7.6% had previously known active cancer, 18.6% had creatinine clearance 30 ≤ CrCl < 60 mL/min, and 87.8% had pulmonary embolism with or without deep venous thrombosis. The major and clinically relevant bleeding rate was 5.4% (15/280) in the rivaroxaban group, 9.4%/(9/96) in the VKA group and 7.2% (5/69) in the heparin/fondaparinux group. The recurrent VTE rate was 1.4% (4/280) in the rivaroxaban group, 3.1% (3/96) in the VKA group and 11.6% (8/69) in the heparin/fondaparinux group. In the propensity score-adjusted samples, major and clinically relevant non-major bleeding (HR 0.37 [95% CI, 0.15 to 0.93], p < 0.05), all-cause death (HR 0.21 [95% CI, 0.06 to 0.66], p < 0.01) and the composite of recurrent VTE, major and clinically relevant non-major bleeding and all-cause mortality (HR 0.35 [95% CI, 0.17 to 0.71], p < 0.01), were significantly lower in the rivaroxaban group compared to the VKA group. Conclusion: In REMOTEV 6-month outcomes are consistent with the findings of the phase 3 randomized trials and post-marketing data, with low rates of major bleeding and symptomatic recurrent VTE.